2018
DOI: 10.1111/ldrp.12169
|View full text |Cite
|
Sign up to set email alerts
|

Using the Number Line to Promote Understanding of Fractions for Struggling Fifth Graders: A Formative Pilot Study

Abstract: A formative pilot study of a fractions intervention was conducted to address the intervention's potential for improving fifth‐grade struggling students’ knowledge of fractions, and to identify any logistical or instructional design issues, before scaling up for a randomized control trial. In the first section, we provide details of the formative pilot study and present preliminary data that demonstrate the potential of the intervention. Intervention lessons—adapted from a commercially available program—emphasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Also, material that did not focus on fractions (e.g., geometry) was eliminated from the lessons. These adapted lessons were piloted and revised prior to implementation in this study (Schumacher et al 2018). Details on how lessons were adapted are described in the pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…Also, material that did not focus on fractions (e.g., geometry) was eliminated from the lessons. These adapted lessons were piloted and revised prior to implementation in this study (Schumacher et al 2018). Details on how lessons were adapted are described in the pilot study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Fazio and colleagues (2016) observed transfer from computerized fraction number line training to other measures of children's fraction magnitude knowledge. Intensive intervention focused on fraction magnitude knowledge can influence both fraction magnitude and fraction arithmetic knowledge (Barbieri et al, 2020;Fuchs et al, 2013;Malone et al, 2019;Schumacher et al, 2018). These interventions have been beneficial…”
Section: Number Line Interventionsmentioning
confidence: 99%
“…Although the number line is more abstract than other continuous models, it is considered one of the most important representations for fractions (Cramer & Wyberg, ). Representing fractions on a number line is essential for students to understand fractions as a number while minimizing the misconception of fractions representing two numbers (Schumacher et al, ). Cramer, Ahrendt, Monson, Wyberg, and Colum () as well as Schumacher et al () found the number line to be a great tool to help children interpret a measurable distance from zero to a fraction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Representing fractions on a number line is essential for students to understand fractions as a number while minimizing the misconception of fractions representing two numbers (Schumacher et al, ). Cramer, Ahrendt, Monson, Wyberg, and Colum () as well as Schumacher et al () found the number line to be a great tool to help children interpret a measurable distance from zero to a fraction. Keijzer and Terwel () found that when that the number line model was central to support the development of fractional strategies, students outperformed a control group who mainly worked individually with the circle as the major fraction model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation